The Influence of Gibberellin-Rich Phytohormones in Monkey Fern (Cibotium barometz) Extract on Mitigating Cherelle Wilt in Cocoa Plants - Saputra, Branmanda Fardhaza; Anggara, Muhammad Tri; Prinandra, Rizkyza; Avianto, Yovi (Jurnal Biologi Tropis, 2025)
Cocoa is one of Indonesia’s main export commodities, but its production has declined due to cherelle wilt disease and environmental stress. Gibberellin hormones have been proven effective in preventing cherelle wilt, but their use is limited by high costs. Extracts from monkey fern leaves offer an economical alternative as a natural source of gibberellin. This study aims to examine the effect of monkey fern extract on the development of cocoa cherelles. The research was conducted from January 2024 to January 2025 on smallholder cocoa farms managed by the Hargomulyo farmer group in Gunungkidul. The treatments compared were foliar spraying of monkey fern extract and a control group. The results showed that the application of monkey fern extract increased the number of healthy cherelles compared to the control. Although total chlorophyll content showed no significant difference, low chlorophyll fluorescence values indicated that the plants experienced heat stress. This condition can disrupt photosynthetic efficiency, but the extract still enhanced carbohydrate accumulation in the seeds. Meanwhile, sucrose, reducing sugar, lipid, and protein contents showed no significant changes.